Model-Informed Precision Dosing for Personalized Ustekinumab Treatment in Plaque Psoriasis - Karine Rodríguez-Fernández; Javier Zarzoso-Foj; Marina Saez-Bello; Almudena Mateu-Puchades; Antonio Martorell-Calatayud; Matilde Merino-Sanjuan; Elena Gras-Colomer; Monica Climente-Martí; Victor Mangas-Sanjuan (MDPI AG, 2024)
Background/Objectives: Implementing model-informed precision dosing (MIPD) strategies guided by population pharmacokinetic/pharmacodynamic (PK/PD) models could enhance the management of inflammatory diseases such as psoriasis. However, the extent of individual experimental data gathered during MIPD significantly influences the uncertainty in estimating individual PK/PD parameters, affecting clinical dose selection decisions. Methods: This study proposes a methodology to individualize ustekinumab (UTK) dosing strategies for 23 Spanish patients with moderate to severe chronic plaque psoriasis., considering the uncertainty of individual parameters within a population PK/PD model. Results: An indirect response model from previous research was used to describe the PK/PD relationship between UTK serum concentrations and the Psoriasis Area and Severity Index (PASI) score. A maximum inhibition drug effect (Imax) model was selected, and a first-order remission constant rate of psoriatic skin lesion (kout = 0.016 d−1) was estimated. Conclusions: The MIPD approach predicted that 35% and 26% of the patients would need an optimized and intensified dosage regimen, respectively, compared to the regimen typically used in clinical practice. This analysis demonstrated its utility as a tool for selecting personalized UTK dosing regimens in clinical practice in order to optimize the probability of achieving targeted clinical outcomes in patients with psoriasis.